OPTIMALISASI SISTEM INFORMASI GEOGRAFIS BANTUAN DANA DESA MENGGUNAKAN DATABASE CLOUD BERBASIS DOKUMEN - Suendri Suendri (UIN Sumatera Utara Medan, 2020)
The purpose of this study is to optimize the Bantuan Dana Desa Geographic Information System in Deli Serdang district, North Sumatra province using a document-based cloud database or abbreviated as NoSQL. The geographic information system for Bantuan Dana Desa that is designed to store large amounts of data and continues to grow each year as long as the policy on Bantuan Dana Desa continues, a high-performance database is needed to support this system to run well. The research method used is Research and Development (R&D) through the stages of Information Collection, System Design, System Validation, System Improvement and System Production. The results of this study concluded that the use of document-based cloud databases can optimize geographic information systems with large data, document-based databases have high flexibility, scalability and performance compared to other relational databases